Analysis of the Interpretation of “Ren” in the Translation of "Lunyu" (Analects of Confucius) - Zeng, Yu (Estudios de Traducción, 2013)
Lunyu, which is a collection of discourses by Confucius and his disciples, is regarded as one of the most important confucian classics. It involves a wide range of subjetcs such as politics, philosophy, literature, education, art, etc. Regarding its Spanish editions, we found three different versions: two of them come from two distinct English editions and the third one is a translation from Chinese by Anne-Hélèn Suárez. In our work, based on the theory of cultural translation and Skopos, we analyze the interpretation of the philosophical concept “Ren” in the translation of Anne-Hélèn Suárez. Through this investigation, we reflect on the problems and try to offer possible solutions too.